Exploring the institutional alternative for requiring traffic impact assessment in the Philippines - Regidor, Jose Regin F. (Philippine Engineering Journal)
The UPNCTSFI Study Team that developed the guidelines for traffic impact assessment (TIA) proposed four mechanisms for institutionalization. These include incorporating TIA within the existing systems such as the Environmental Impact Analysis (EIA) required for environmentally critical projects and local government processes that give clearance for developments to be undertaken including those that will necessitate a change in the land use. This paper expounds on these proposed mechanisms, recommends a practical set-up and tackles the prerequisites for TIA to be applied in the Philippines. Capability building on the part of the government is discussed thoroughly, as well as the issues of accreditation and costs associated with TIA. As such the paper is able to achieve its primary objective of providing a comprehensive discussion on the institutionalization of TIA in the Philippines.